1998
DOI: 10.1046/j.1365-2265.1998.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased body weight associated with prolactin secreting pituitary adenomas: weight loss with normalization of prolactin levels

Abstract: Weight gain and elevated body weight are frequently associated with prolactinomas regardless of a mass effect on the hypothalamus or pituitary function. In this series, weight loss was recorded in 70% of prolactinomas patients and in 90% of male patients who normalized their prolactin levels. We propose the inclusion of hyperprolactinaemia in the differential diagnosis of endocrine obesity and weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
164
4
13

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(190 citation statements)
references
References 23 publications
9
164
4
13
Order By: Relevance
“…Prolactinomas producing high levels of prolactin are typically associated with weight gain 4. In addition, a study in obese women found that increased BMI and VAT are associated with an increased prolactin secretion rate 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolactinomas producing high levels of prolactin are typically associated with weight gain 4. In addition, a study in obese women found that increased BMI and VAT are associated with an increased prolactin secretion rate 8.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, elevation of prolactin is associated with increased food intake and body weight 3. In humans with prolactinomas, weight gain is often a prominent feature and is reversible with prolactin‐lowering therapy 4. Other metabolic abnormalities seen in prolactinomas include insulin resistance and dyslipidemia 5.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Subsequent weight loss after treatment with dopamine agonists has also been reported, 3,4 although this has been disputed in one study that showed weight gain after treatment. 5 We therefore undertook a retrospective study of 37 patients with prolactinoma (22 macroprolactinoma and 15 with microprolactinoma, defined by MRI scan of tumour size) and related body weight changes over 24 months to changes in serum and prolactin concentrations.…”
mentioning
confidence: 99%
“…Манифестация заболевания в описан-ном нами клиническом случае совпала с рез-ким снижением массы тела, что могло быть обусловлено развитием диэнцефальной ка-хексии вследствие вовлечения гипоталамуса в патологический процесс супраселлярно растущей опухолью. Напротив, в большин-стве случаев манифестация гиперпролакти-немии сопровождается повышением массы тела [14,15]. Убедительных клинико-лабора-торных данных за наличие гипокортицизма в описанном нами случае выявлено не было.…”
Section: Discussionunclassified